Penggunaan Law Analyzer dalam Pengharmonisasian Rancangan Peraturan Perundang-Undangan : Senjakala Jabatan Fungsional Perancang Peraturan Perundang-Undangan - Eka N.A.M. Sihombing; Cynthia Hadita; Muhammad Aufa Abdillah Sihombing (Badan Strategi Kebijakan Hukum, 2024)
The existence of artificial intelligence technology (artificial intelligence) has brought significant changes in various fields, including laws and regulations, in addition to providing convenience but AI also has the potential to be a threat to the human profession. One of them is the presence of law analyzer, as one of the AI-based innovations, capable of analyzing, harmonizing, and providing recommendations for improvement in draft laws and regulations efficiently and accurately which can affect the role of the drafters of laws and regulations. The research method used is sociological research with qualitative analysis, sociological and comparative approaches. This study aims to explore the impact of the use of law analyzer on the role and function of functional positions of legislative drafters. The results of the study show that although law analyzer can improve the speed and quality of the regulatory harmonization process, its existence also raises concerns about the shift in the role of Legislative Drafters. AI technology has the potential to take over tasks previously performed by humans, so Legislative Drafter are required to upgrade skills so that they are not replaced by the presence of AI.